Hysteretic response of an innovative blind bolted endplate connection to concrete filled tubular columns - Wang, Zhiyu (2012)
Concrete filled steel tubular (CFT) columns can employ the advantages of both materials: steel and concrete. Connection to such columns, however, is problematic. This is especially so if the required connection is both bolted and moment-resisting.